Ultrahigh Color Rendering in RGB Perovskite Micro‐Light‐Emitting Diode Arrays with Resonance‐Enhanced Photon Recycling for Next Generation Displays. Issue 1 (31st October 2021) - Liang, Jie; Du, Yuxiang; Wang, Kang; Ren, Ang; Dong, Xinyu; Zhang, Chunhuan; Tang, Ji; Yan, Yongli; Zhao, Yong Sheng
Abstract: Light sources with high color purity are promising for revolutionizing traditional displays because of their wide achievable color gamut, high contrast ratio, and good color saturation. The demand for next‐generation displays has driven the development of the optoelectronic materials with narrow linewidth. Until now, most optoelectronic materials usually give emission with full width at half maximum exceeding 30 nm. The lack of a general approach to further improving the color purity has limited their applications for next‐generation displays. Here, a universal resonance‐enhanced photon recycling strategy is developed to realize current‐driven displays with unprecedented high color rendering based on the perovskite light‐emitting diode (LED) arrays in distributed Bragg reflector (DBR) cavity. Benefiting from the outstanding optoelectronic properties and solution processability, perovskites are processed into micro‐LED arrays through a screen‐printing technology. The light output from individual micro‐LED is strongly modulated by resonance‐enhanced photon recycling derived from the cavity structure, leading to significant spectral narrowing and directional emission. On this basis, unprecedented high‐color‐purity is achieved in a prototype of current‐driven display panels. The outstanding performance of red, green, and blue (RGB) micro‐LED arrays with resonance‐enhanced photon recycling provides a deep insight into the design concepts and device structures for next‐generation display technology. Abstract : Unprecedented high‐color‐purity displays are demonstrated on new‐type display panels composed of all‐color perovskite micro‐LED arrays. Through integrating distributed Bragg reflector structures into the display panels, the light output from the micro‐LED pixels is modulated by the microcavity resonance‐enhanced photon recycling, and the color purity of the display panels is significantly improved to fulfil the requirements of next‐generation displays.